Optimization of protocols for the use of Banana SSR markers in genome analysis of Abaca (Musa textilis Nee) - Solito Melissa T. (2002)
Abaca (Musa textilis Nee) is an endemic species to the Philippines. The Philippines is considered as the center pf origin of abaca. It holds the largest collection of abaca accessions in the world. However, due to the decline in the economic importance of the crop, very limited funds are available for its research, and almost nil for biotechnology. Being closely related to edible bananas, it is possible that advances in research on banana may be used in abaca. Thus, this study was conducted to develop the optimized conditions for sample sequence repeat (SSR) of microsatellite analysis in abaca using SSR primers previously developed for banana. The conditions that were manipulated for the optimization included annealing temperature, template DNA concentration, number of repeat cycles in the PCR process and the run time of PAGE. The optimized conditions were tested using 28 banana SSR primer pairs. Out of the 28 banana SSR primer pairs tested, only five primers worked well for abaca. The optimized conditions for SSR analysis of abaca are as follows: 52-600C annealing temperature, 30-35 PCR cycles, 20-30 ng template DNA concentration, and 45 min PAGE run. The five primers identified that worked well for abaca are: Ma1/016, Ma1/032, Ma2/4, Ma 3/103, and Ma3/139
Thesis (BS Biology) -- University of the Philippines Mindanao, 2002